MUHAMMADIYAH: GERAKAN MODERNISME ISLAM - Nashir, Haedar (Universitas Muhammadiyah Surakarta, 2016)
This paper reveals about the Muhammadiyah movement which is very strategic, it is reformist-modern Islamic movement that takes the mid position with Islamic view âprogressive fondationâ. Â Muhammadiyah view can be used as the fondation of the modern world enters a new era of the twenty-first century, which has entered the second century with the theme